Activation of NR1H3 attenuates the severity of septic myocardial injury by inhibiting NLRP3 inflammasome - Chao Deng; Qiong Liu; Huadong Zhao; Lu Qian; Wangrui Lei; Wenwen Yang; Zhenxing Liang; Ye Tian; Shaofei Zhang; Changyu Wang; Ying Chen; Yang Yang (Wiley, 2023)
Abstract Most sepsis deaths are due to the development of multiple organ failure, in which heart failure is a recognized manifestation of sepsis. To date, the role of liver X receptors α (NR1H3) in sepsis is still uncertain. Here, we hypothesized that NR1H3 mediates multiple essential sepsis‐related signalings to attenuate septic heart failure. Adult male C57BL/6 or Balbc mice and HL‐1 myocardial cell line were performed for in vivo and in vitro experiments, respectively. NR1H3 knockout mice or NR1H3 agonist T0901317 was applied to evaluate the impact of NR1H3 on septic heart failure. We found decreased myocardial expression levels of NR1H3‐related molecules while increased NLRP3 level in septic mice. NR1H3 knockout worsensed cardiac dysfunction and injury in mice subjected to cecal ligation and puncture (CLP), in association with exacerbated NLRP3‐mediated inflammation, oxidative stress, mitochondrial dysfunction, endoplasmic reticulum stress, and apoptosis‐related markers. The administration of T0901317 reduced systemic infection and improve cardiac dysfunction in septic mice. Moreover, Co‐IP assays, luciferase reporter assays, and chromatin immunoprecipitation analysis, confirmed that NR1H3 directly repressed NLRP3 activity. Finally, RNA‐seq detection further clarified an overview of the roles of NR1H3 in sepsis. In general, our findings indicate that NR1H3 had a significant protective effect against sepsis and sepsis‐induced heart failure.